Human CD14+ cells loaded with Paclitaxel inhibit in vitro cell proliferation of glioblastoma - Bonomi, Arianna; Lisini, Daniela; Navone, Stefania Elena; Frigerio, Simona; Dossena, Marta; Ciusani, Emilio; Rampini, Paolo; Marfia, Giovanni; Coccè, Valentina; Cavicchini, Loredana; Sisto, Francesca; Parati, Eugenio; et al. (Cytotherapy (Oxford, England), 2015)
In attempting to develop new strategies to circumvent the immunosuppression associated with glioblastoma (GB), novel approaches have been designed using dendritic cell (DC)-based vaccination, which is considered a promising strategy to attack high-grade glioma. In previous studies, we demonstrated that human mesenchymal stromal cells without genetic manipulation but primed with Paclitaxel (PTX) acquire a potent anti-tumor activity, providing an interesting new biological approach for drug delivery. On the basis of these results, we here investigated whether both CD14+ and their derived DCs may behave like mesenchymal stromal cells acquiring anti-tumor activity on priming with PTX. Human CD14+ cells were isolated from peripheral blood. Fluorescence-activated cell sorter analysis was performed to determine the purity of CD14+ and their differentiation into mature DCs. Cells were primed by incubation with 1 μg/mL of PTX for 24 h, and the PTX released by cells was assessed by mass spectrometry analysis. Anti-tumor activity was checked by testing the conditioned medium (CM) on the proliferation of U87 MG, a GB cell line. Both CD14+ and DCs were able to incorporate PTX and release the drug in the CM in a time-dependent manner (maximal release over 24 h). The addition of CM from CD14+ and DCs loaded with PTX strongly inhibits proliferation of U87 MG cells. Our results are the first demonstration that peripheral blood–derived CD14+ and DCs, in addition to their application for immunotherapy for GB, could also be used to delivery anti-cancer drugs, such as PTX, to kill GB cells.